Isotopic effect in half-wavelength-crystal channeling of relativistic ions; Physics Letters B; Vol. 802 - Bogdanov O. V. Oleg Viktorovich; Pivovarov Yu. L. Yuriy Leonidovich; Tukhfatullin T. A. Timur Ahatovich; Geissel H. Hans; Kuzminchuk-Feuerstein N. Natalya; Purushothaman S. Sivaji; Scheidenberger Ch. Christoph (2020, 2020)
Title screen